Guns, School Shooters, and School Safety: What We Know and Directions for Change. Issue 2 (3rd July 2021) - Flannery, Daniel J.; Fox, James Alan; Wallace, Lacey; Mulvey, Edward; Modzeleski, William
Abstract: We summarize current data and understanding about the prevalence of gun violence at schools and risk of rampage school shootings. Following that comes a discussion of gun availability among youth and strategies and practices in the United States and abroad that have been implemented to limit access to firearms for minors. Next, we review the current evidence for arming school teachers, a strategy that could also increase the number of firearms in schools. We then focus on three specific strategies that schools have implemented to reduce school shootings and improve school safety: (a) addressing the role of mental health in school shootings and violence perpetration; (b) implementing multidisciplinary threat assessment protocols; and (c) target hardening and utilizing school resource officers. Based on available evidence, a public health approach to addressing firearm violence in schools is the most effective way to prevent school shootings, even if these effects are indirect through improvements in student social competence and positive school climate. Finally, we offer some recommendations for future practice, policy and research. Impact Statement Based on the available evidence, singular approaches like target hardening or utilizing SROs will not reduce risk for school shootings and may lead to other deleterious effects. A public health approach that emphasizes student social–emotional learning and improved school climate may indirectly reduce firearm violence. Policies that limit youth access to firearms may also help to lower the risk of gun violence at school.